2008
DOI: 10.1111/j.1651-2227.2008.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of individual room on rehospitalization and health service utilization in preterms after discharge

Abstract: The availability of individual rooms that allows maternal presence and participation during the hospitalization of the mother's preterm infant, is correlated with lower rates of rehospitalization and healthcare applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…3 Further, current recommendations for NICU design include construction of private space to reduce environmental stimulation to the infant and support family involvement. 8 Positive staff and caregiver perceptions, 9-11 decreased noise levels and nosocomial infections, 12, 13 and lower rates of readmission in the months after discharge 14 were reported following NICU renovation to private rooms. A randomized clinical trial conducted in Sweden reported reductions in length of stay among infants assigned to single family rooms, consisting of private space for the family and infant, and in which parents were required to be present from admission to discharge.…”
mentioning
confidence: 99%
“…3 Further, current recommendations for NICU design include construction of private space to reduce environmental stimulation to the infant and support family involvement. 8 Positive staff and caregiver perceptions, 9-11 decreased noise levels and nosocomial infections, 12, 13 and lower rates of readmission in the months after discharge 14 were reported following NICU renovation to private rooms. A randomized clinical trial conducted in Sweden reported reductions in length of stay among infants assigned to single family rooms, consisting of private space for the family and infant, and in which parents were required to be present from admission to discharge.…”
mentioning
confidence: 99%
“…Parental satisfaction with care in a single-family room NICU is higher than in the traditional open-bay NICU [41]. Furthermore, the provision of suitable facilities to enable a parent to stay overnight or even to sit comfortably and in close contact with their babies can enhance breastfeeding success [42]; reduce length of hospital stays [43] and rehospitalisation rates [44]; facilitate bonding and promote access to clinical staff [14] and reduce parental and infant stress levels [45]. Communal areas to obtain peer support and alleviate loneliness through the sharing of experiences are also identified as beneficial [25].…”
Section: Discussionmentioning
confidence: 99%
“…Care-by-parent programs in level 2 and 3 neonatal units have been reported to reduce the length of stay by 3.2-5.3 days, 7,9,10 decrease hospital readmission, 5 and improve infant outcomes, such as the rate of breastfeeding and weight gain, 6 in cohort studies and one randomized controlled trial. Although the long-term effects of care-byparent programs have not been investigated, increased parent education and interaction between parents and their preterm infant was reported to improve infant behaviour and longterm cognitive development in a cohort study 11 and randomized controlled trial.…”
Section: What Are the Benefits Of This Model Of Care?mentioning
confidence: 99%